2019
DOI: 10.1097/corr.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Does Accelerometer-based Navigation Have Any Clinical Benefit Compared with Conventional TKA? A Systematic Review

Abstract: Background Accelerometer-based navigation is a handheld navigation tool that was introduced to offer a simpler technique compared with more-cumbersome computer-assisted surgery (CAS). Considering the increasing number of adopters, it seems important to evaluate the potential clinical benefits of this technology compared with conventional TKA. Questions/purposes In this systematic review, we asked: (1) Is accelerometer-based navigation more accurate than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Budhiparama et al have described the results of the main studies about accelerometers in a systematic review [ 53 ]. Five of nine studies favored accelerometer-based navigation for the restoration of HKA [ 54 , 55 , 56 , 57 , 58 ], while four of nine studies found no differences between the study groups [ 59 , 60 , 61 , 62 ].…”
Section: Accelerometermentioning
confidence: 99%
See 2 more Smart Citations
“…Budhiparama et al have described the results of the main studies about accelerometers in a systematic review [ 53 ]. Five of nine studies favored accelerometer-based navigation for the restoration of HKA [ 54 , 55 , 56 , 57 , 58 ], while four of nine studies found no differences between the study groups [ 59 , 60 , 61 , 62 ].…”
Section: Accelerometermentioning
confidence: 99%
“…There was no significant difference in functional knee score at short term follow-up in the iASSIST group compared with the conventional group [ 63 ]. No studies have demonstrated better clinical outcomes with accelerometer-based navigation compared with conventional technique TKA [ 53 ].…”
Section: Accelerometermentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the fact that ABN does not significantly alter the surgical process used in conventional TKA, but it just provides accurate alignment information during the procedure. Recently, a systematic review by Budhiparama et al [ 35 ] also found conflicting evidence as to whether ABN device decreases the number of outliers or improves the postoperative alignment to a clinically important level. On the other hand, using ABN might be associated with prolonged operative time [ 8 ] and additional cost of US$850–$1000 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Budhiparama et al . (2019) published a review article on handheld navigation systems, including 11 manuscripts and 1298 TKA patients, to compare their accuracy, functional outcomes, and surgical times with the conventional technique 33 . However, there was no evidence to conclude that there was an improvement in clinical or patient‐reported outcome measures with handheld systems, but increased expense was demonstrated, with the longer operative times.…”
Section: Computer‐assisted Total Knee Arthroplasty Systemsmentioning
confidence: 99%